ANALISIS PENGARUH FAKTOR-FAKTOR PRIBADI IBU RUMAH TANGGA DALAM KEPUTUSAN PEMBELIAN MAKANAN DI PASAR MODERN (Studi Pada Ibu Rumah Tangga di Komplek Perumahan Mandiri Lestari Banjarmasin) (At-Taradhi Jurnal Studi Ekonomi, 2014)
The aim of this paper is to analyze the effect of housewifesprivate factors (age, occupation, family revenue, family expenditure, the level of family life cycle, lifestyle, and personality) simultanly and partially as well as to observe the most dominant effect in food purchases decision in modern market. This paper was conducted on Perumahan Mandiri Lestari, Sultan Adam, Banjarmasin. Sampling techniques in this paper is non-probability sampling, namely judgment sampling. Data analysis was conducted with descriptive analysis techniques using multiple linear regression model. According to the result of this paper, the conclusion is that the private factor which affect food purchases decision in modern market is family revenue.